Linear Control Systems on Homogeneous Spaces of the Heisenberg Group - Da Silva, Adriano; Kizil, Eyup; Duman, Okan (SPRINGER/PLENUM PUBLISHERS, 2023)
Let H denote the 3-dimensional Heisenberg Lie group. The main purpose of this paper is to classify all possible linear control systems on the homogeneous spaces of H through its closed subgroups. We expose a detailed study on the control behavior (i.e., controllability property and control sets) of some particular dynamics evolving on non simply connected homogeneous (state) spaces of dimension two and three.
Keywords: Linear control systems; Heisenberg group; Homogeneous spaces; Automation & Control Systems; Mathematics